Are statins anti-inflammatory? - Ridker Paul M; Blake Gavin J (Current Controlled Trials in Cardiovascular Medicine, 2000)
Abstract Large scale clinical trials demonstrate significant reductions in cardiovascular event rates with statin therapy. The observed benefit of statin therapy, however, may be larger in these trials than that expected on the basis of lipid lowering alone. Emerging evidence from both clinical trials and basic science studies suggest that statins have anti-inflammatory properties, which may additionally lead to clinical efficacy. Measurement of markers of inflammation such as high sensitivity C-reactive protein in addition to lipid parameters may help identify those patients who will benefit most from statin therapy.